POLA KEPEMIMPINAN MUSA: MENINGKATKAN KUALITAS PELAYANAN GEREJA DI ERA DIGITAL - Situmorang, Sitor; Hermanto, Yanto Paulus (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
In facing cultural and technological shifts in the digital era, there is a phenomenon where congregations tend to shift focus from service goals which should honor God towards achieving self-satisfaction. This shows a shift in values ​​that influence the practice of church services, which should be in accordance with God's will and which should honor and glorify God. Therefore, a good and proportional leadership pattern is needed, such as the leadership pattern shown by Moses in the Bible. Through these conditions, this research tries to analyze a "Mosaic leadership pattern: improving the quality of church services in the digital era." The aim of this research is to explore how the Moses leadership pattern can be applied to improve the quality of church services in the digital era, as well as the implications for church leaders in improving their service practices amidst the challenges of an ever-evolving era. The research method used in this research is a descriptive qualitative method approach. In this research, the author wants to discuss how church services are in the digital era and what Moses' leadership pattern was in leading the Israelites and how Moses' leadership pattern can be applied to improve the quality of church services in the digital era.